2023
DOI: 10.1172/jci.insight.167890
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 convalescent plasma boosts early antibody titer and does not influence the adaptive immune response

Abstract: Multiple randomized, controlled clinical trials have yielded discordant results regarding the efficacy of convalescent plasma in outpatients, with some showing an approximate two-fold reduction in risk and others showing no effect. We quantified binding and neutralizing antibody levels in 492 of the 511 participants from the C3PO trial of a single unit of COVID-19 convalescent plasma (CCP) vs. saline infusion. In a subset of 70 participants, peripheral blood mononuclear cells were obtained to define the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Again, we found no worsening of outcomes in the study‐eligible transfused population during this period nor among a subgroup of unvaccinated transfusion recipients; the latter notable because some recipients of blood products have expressed concern about the passive transfer of SARS‐CoV‐2 antigens or antibodies 19 . Our findings are also consistent with clinical trial and observational data supporting the safety of CCP and laboratory‐based studies that did not find evidence of an impact of CCP transfusion on the adaptive immune response of recipients 38 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Again, we found no worsening of outcomes in the study‐eligible transfused population during this period nor among a subgroup of unvaccinated transfusion recipients; the latter notable because some recipients of blood products have expressed concern about the passive transfer of SARS‐CoV‐2 antigens or antibodies 19 . Our findings are also consistent with clinical trial and observational data supporting the safety of CCP and laboratory‐based studies that did not find evidence of an impact of CCP transfusion on the adaptive immune response of recipients 38 …”
Section: Discussionsupporting
confidence: 82%
“…19 Our findings are also consistent with clinical trial and observational data supporting the safety of CCP and laboratory-based studies that did not find evidence of an impact of CCP transfusion on the adaptive immune response of recipients. 38 We focused on evaluating outcomes among transfusion recipients during study periods with known variation in donor SARS-CoV-2 infection and vaccination. [10][11][12] However, it is worth recognizing that other factors occurring Note: Adjusted odds ratios (aOR) with 95% confidence interval presented for oxygen requirements and thromboses in pre-vaccine and post-vaccine study periods relative to the Pre-COVID period adjusting for demographics and comorbidities presented in Table 1 and number of plasma, platelet, and RBC units.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings show that transfusion of CCP, as compared to control plasma, was not associated with differences in the total antibody level immune response in recipients, reassuring for the immunological safety of CCP in humans. The C3PO convalescent plasma study also demonstrated no antibody level difference between CCP and saline infusions(14, 18).…”
Section: Discussionmentioning
confidence: 90%
“…Finally, there was concern that CCP administration would blunt the immune response to SARS-CoV-2 but recent studies of participants in the C3PO trial showed no evidence that adaptive immune responses were affected. 64 Our systematic review has some limitations. The first is that most RCTs included CCP safety evaluation as secondary outcome, and this aspect could have influenced the accuracy of data recording.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have provided evidence that CCP with such antibodies was not harmful, 63 our results provide additional reassurance this regard. Finally, there was concern that CCP administration would blunt the immune response to SARS‐CoV‐2 but recent studies of participants in the C3PO trial showed no evidence that adaptive immune responses were affected 64 …”
Section: Discussionmentioning
confidence: 99%